(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study attempts to investigate the livestock in the Erbil governorate between 1991 and 2003. Some factors have an impact on livestock. The studies examine the data and information which collected by the government to show the circumstances of livestock. There are many factors impacting on the circumstances of livestock, Including pasture, workforce, political causes, economic blockade, civil war, and the oil for food program. Following the 1991 uprising, the majority of poultry farms closed, but by providing what they needed after the oil for food program, they restarted production, causing meat prices to fall. A number of new projects, such as dairy cattle, fish farming, and beekeeping, were also established, leading to a gradual increase in the number of animals during the research.